Single puncture approach guided by transesophageal echocardiography for atrial fibrillation ablation in a patient with prior percutaneous septal closure: case report. Issue 4 (12th April 2023) - Oliveira, Mário; Sousa, Lidia; Trindade, Ana; da Silva, Nogueira
Abstract: Background: Atrial septal defect (ASD) is associated with a risk of developing atrial fibrillation (AF) higher than in the general population, even after percutaneous or surgical septal closure. Catheter ablation is an effective treatment strategy for preventing recurrences and reducing the AF burden. However, electrophysiologists are faced with technical difficulties and the risk of complications with the left atrium access in patients with prior ASD percutaneous closure. Case summary: We report a case of a patient with highly symptomatic paroxysmal AF, with an ASD, closed percutaneously many years before, who underwent a successful catheter AF ablation, using a single transeptal (TSP) approach guided by transesophageal echocardiography (TEE). Discussion: In patients with ASD and an occluder device implanted, there is a potential risk for septal tear during the TSP passage, device dislodgement, or thrombus formation on the device. Atrial fibrillation ablation in this subset of patients has often been protracted and scarcely reported. TEE and intra-cardiac echocardiography have been increasingly used for interventional procedure guidance during AF ablation. As described here, AF ablation using a simplified single TSP guided by TEE is feasible, safe, and effective after device ASD closure.